ANÁLOGOS SINTÉTICOS INSULINOMIMÉTICOS A PARTIR DE NOVOS COMPOSTOS BASEADOS EM ÍONS VANÁDIO(III) E VANADILO (OVIV)+2 - Carvalho, Silas Helede de; Dantas, Jaqueline S.; Faganello, Natali L.; Nascimento, João P. C.; Cabeza, Natalia Apª.; Anjos, Ademir Dos (ANAIS DO ENIC, 2020)
-